Diacylglycerol Kinases as Emerging Potential Drug Targets for a Variety of Diseases: An Update - Sakane, Fumio; Mizuno, Satoru; Komenoi, Suguru (Frontiers in Cell and Developmental Biology, 2016)
Ten mammalian diacylglycerol kinase (DGK) isozymes (alpha–kappa) have been identified to date. Our previous review noted that several DGK isozymes can serve as potential drug targets for cancer, epilepsy, autoimmunity, cardiac hypertrophy, hypertension and type II diabetes (Curr. Drug Targets 9, 626–640 (2008)). Since then, recent genome-wide association studies have implied several new possible relationships between DGK isozymes and diseases. For example, DGKtheta and DGKkappa have been suggested to be associated with susceptibility to Parkinson’s disease and hypospadias, respectively. In addition, the DGKeta gene has been repeatedly identified as a bipolar disorder (BPD) susceptibility gene. Intriguingly, we found that DGKeta-knockout mice showed lithium (BPD remedy)-sensitive mania-like behaviors, suggesting that DGKeta is one of key enzymes of the etiology of BPD. Because DGKs are potential drug targets for a wide variety of diseases, the development of DGK isozyme-specific inhibitors/activators has been eagerly awaited. Recently, we have identified DGKalpha-selective inhibitors. Because DGKalpha has both pro-tumoral and anti-immunogenic properties, the DGKalpha-selective inhibitors would simultaneously have anti-tumoral and pro-immunogenic (anti-tumor immunogenic) effects. Although the ten DGK isozymes are highly similar to each other, our current results have encouraged us to identify and develop specific inhibitors/activators against every DGK isozyme that can be effective regulators and drugs against a wide variety of physiological events and diseases.